Lighting up our waterways: Impacts of a current mitigation strategy on riparian bats ... - Hooker, Jack; Lintott, Paul; Stone, Emma (Zenodo, 2022)
(Uploaded by Plazi for the Bat Literature Project) Increasing levels of artificial light at night (ALAN) are a major threat to global biodiversity and can have negative impacts on a wide variety of organisms and their ecosystems. Nocturnal species such as bats are highly vulnerable to the detrimental effects of ALAN. A variety of lighting management strategies have been adopted to minimise the impacts of ALAN on wildlife, however relatively little is known about their effectiveness. Using an experimental approach, we provide the first evidence of negative impacts of part-night lighting (PNL) strategies on bats. Feeding activity of Myotis spp. was reduced along rivers exposed to PNL despite no reduction in overall bat activity. We also provide the first evidence of negative effects of PNL on both feeding and activity for Pipistrellus pipistrellus which has previously been recorded feeding under artificial light. ...